A landscape of nonsupersymmetric AdS vacua on coset manifolds - Koerber, Paul; Körs, Simon (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We construct new families of nonsupersymmetric sourceless type IIA AdS4 vacua on those coset manifolds that also admit supersymmetric solutions. We investigate the spectrum of left-invariant modes and find that most, but not all, of the vacua are stable under these fluctuations. Generically, there are also no massless moduli.